Spiritual Mental Development Through Hindu Education For HIV AIDS - Inay Bhagwandas (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
Mental guidance refers to the formation of a complete personality with strong faith and physical strength. If a person's mental state does not get attention it will bring negative impacts. The fragility of one's mental endurance can be overcome by increasing the spiritual deepening of religion. In connection with this optimization of Hindu religious education is very influential in the development of mental and spiritual, especially among people with HIV AIDS. People with HIV AIDS must understand and implement religious teachings so as to avoid negative actions and harm themselves and others. Research on the mental and spiritual development of people with HIV AIDS through the Hindu religious education approach is important to be carried out, in addition to having never been investigated, it can also provide an illustration of tackling the spread of HIV AIDS and increasing the spirit of life for sufferers.